Species diversity and spatial distribution of mosquitoes (Diptera: Culicidae) from La Isla Amazon Park, Napo Province, Ecuador - Jacome, Linda (2023)
Introduction: Vector-borne diseases are prevalent in the Amazon and Coastal regions of Ecuador. However, there is a scarcity of mosquito ecology studies in these areas. The most recent list of species reported for the country comprises 8 tribes, 22 genera, and 200 species. Objectives: To document the Culicidae species found in La Isla Amazon Park, Napo, Ecuador, including those with epidemiological significance; and to analyze their composition, abundance, and diversity, focusing on larval habitats during the dry and rainy periods. Methods: We evaluated different larval habitats, considering collection duration as the primary criterion. We used CDC and Shannon traps to collect adult mosquitoes during both rainy and dry periods. To assess sampling effort, we used accumulation curves and non-parametric estimators of species richness, while we employed Hill numbers to determine diversity. Additionally, we used the Berger-Parker and Pielou indices to evaluate species dominance and evenness. We conducted cluster analysis and ANOSIM tests to assess the similarity between habitats and the differences in taxonomic composition between periods. Results: We collected a total of 802 individuals from 15 species and 4 taxonomic units, 5 genera, and 4 tribes. Notably, this may be the first records of Wyeomyia felicia Dyar & Núñez Tovar and Culex derivator Dyar & Knab from Ecuador. Additionally, the presence of Culex dunni Dyar and Psorophora ferox von Humboldt (both recog-nized as vectors) was correlated with increased rainfall. Conclusions: The abundance of mosquitoes, including potential vector species, increased during the rainy sea-son, indicating a higher risk of pathogen transmission. However, the relationship between rainfall amount and diversity patterns is not well-defined.